OFFICIALS’ PERFORMANCE IN THE DIGITAL TRANSFORMATION OF GOVERNMENT: DO WE EXPECT TOO MUCH? - Uly Artha Sirait, Laila Refiana Said, Maya Sari Dewi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study analyzes the influence of E-government, Digital Competence, and Digital Transformation on officials' Performance at the Ministry of Communication and Information Technology of the Republic of Indonesia. The research method was quantitative empirical research using a survey, combined with interviews and observation. The measurement scale used ordinal data. Partial Least Square - Structural Equation Modeling (PLS-SEM) method was applied using SmartPLS 3 in analyzing the data. This study shows that E-government and Digital Competence affect Performance through Digital Transformation as a mediating variable. Digital Transformation partially mediates the influence of E-government on Performance. On the other hand, Digital Transformation has fully mediated the influence of Digital Competence on Performance. Digital competence is considered part of digital transformation. Government officials' performance tends to increase due to enforced policy (e-government and digital transformation of government), not because of their inner motivation (digital competence). This study fills the knowledge gap of government officials' performance to represent the organization's ability to deliver high-value and real-time services in a disruptive era.